A Cultural History of Crocodiles in the Philippines: Towards a New Peace Pact?. (1st May 2011) - Van der Ploeg, Jan; van Weerd, Merlijn; Persoon, Gerard A.
Abstract : Crocodiles have an image problem in the Philippines. In mainstream Filipino society crocodiles are considered dangerous man-eaters, and compared with corrupt government officials or selfish basketball players. It is often argued that these negative public attitudes towards crocodiles make in-situ crocodile conservation impossible in the Philippines. Only by securing economic benefits for rural communities through sustainable use can crocodiles be conserved. In this paper we contest this narrow utilitarian view. In fact indigenous peoples in the northern Sierra Madre have a history of co-existence with crocodiles. In the pre-Hispanic Philippines people feared and revered crocodiles: specific rules regulated the relationship between crocodiles and people. Traditional beliefs and practices enable people to share the landscape with a potentially dangerous carnivore. This forces us to rethink conventional conservation strategies that focus narrowly on economic values.